Mast cell in infantile hemangioma - Xia, Meng; Liu, Wenying; Hou, Fang (Frontiers in Oncology, 2024)
Infantile hemangioma (IH) is the most common benign vascular tumor characterized by three phases -proliferation, early involution and late involution. Mast cells (MCs) play an important role in allergic reactions and numerous diseases, including tumors. While the mechanisms underlying MCs migration, activation and function in the life cycle of IH remain unclear, previous studies suggested that MCs circulate through the vasculature and migrate into IH, and subsequently mature and get activated. Estradiol (E2) emerges as a potential attractant for MC migration into IH and their subsequent activation. In various stages of IH, activated MCs secrete both proangiogenic and antiangiogenic modulators, absorbed by various cells adjacent to them. Imbalances in these modulators may contribute to IH proliferation and involution.